Exploring Child Abuse Revealed in Jennette McCurdy's I'm Glad My Mom Died - Kamila, Alvi; M. Litaay, Adeline Grace (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This research discusses child abuse in Jennette McCurdy’s I’m Glad My Mom Died. This study aims to analyze the cause, types, and impacts using the theory of child abuse by John Briere. The method that is used in this research is descriptive qualitative method. This thesis also uses the psychological approach. Based on the analysis the cause of the abuse is the obsession of Jennette’s mother to be an actress, which failed. In Jennette McCurdy’s I’m Glad My Mom Died, the writer found three types of abuse experienced by Jennette: physical abuse, psychological/emotional abuse, and child neglect. The example of physical abuse found in the novel are: forced to do an extreme diet and beauty treatment that causes harm to Jennette’s body. The psychological/emotional abuse found in the analysis is divided into eight parts: rejecting, degrading / devaluing, terrorizing, isolating, and corrupting, denying essential stimulation, emotional responsiveness, or availability, the last one is unreliable and inconsistent parenting. Furthermore, the child neglect found is divided into four types: physical neglect, emotional neglect, educational neglect and medical facility neglect. There are three impacts of child abuse found in the analysis: psychological issues, personality development, and physical health. The example of psychological issues found in the novel are: eating disorders, depression and anxiety. The instances of personality development found in the novel are: turning into a bitter person, cannot manage jealousy and temperamental. The example of physical health found in the novel are: issues with alcohol, illness, and bulimia. After experiencing that abuse, it influences Jennette such as struggles with self-image, mental health issues, the impact of career choices, desires for healing, advocacy, and sharing about mental health issues.